2008
DOI: 10.1016/j.jadohealth.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Receptivity to Alcohol Marketing Predicts Initiation of Alcohol Use

Abstract: Purpose: This longitudinal study examined the influence of alcohol advertising and promotions on the initiation of alcohol use. A measure of receptivity to alcohol marketing was developed from research about tobacco marketing. Recall and recognition of alcohol brand names were also examined. Methods: Data were obtained from in-class surveys of sixth, seventh, and eighth graders at baseline and 12-month follow-up. Participants who were classified as never drinkers at baseline (n ϭ 1,080) comprised the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 41 publications
3
106
0
1
Order By: Relevance
“…Although there was no direct endorsement of tobacco brands, their presence in music videos is arguably entirely unnecessary and illegal under the 2002 Act 50. In light of consistent evidence, including longitudinal studies, that exposure to tobacco 16, 18, 52 and alcohol 10, 11, 12, 13, 53 promotion and advertising encourages the uptake of smoking and alcohol use in adolescents, our concern is that young people will emulate these smoking and drinking behaviours and therefore that music videos containing alcohol and tobacco content should be restricted. Tobacco and alcohol marketing opportunities should be controlled more tightly in social and user‐generated media, and official music video makers and distributors should be proactive in working towards this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no direct endorsement of tobacco brands, their presence in music videos is arguably entirely unnecessary and illegal under the 2002 Act 50. In light of consistent evidence, including longitudinal studies, that exposure to tobacco 16, 18, 52 and alcohol 10, 11, 12, 13, 53 promotion and advertising encourages the uptake of smoking and alcohol use in adolescents, our concern is that young people will emulate these smoking and drinking behaviours and therefore that music videos containing alcohol and tobacco content should be restricted. Tobacco and alcohol marketing opportunities should be controlled more tightly in social and user‐generated media, and official music video makers and distributors should be proactive in working towards this goal.…”
Section: Discussionmentioning
confidence: 99%
“…5,15 It was anticipated that adolescents who like alcohol advertisements will be more likely to elaborate on the content of the ads (eg, imagine themselves in the scene), and as a result, they will be more likely to be persuaded to try the product. 16,17 Studies on copy testing by advertisers have shown that liking of advertisements is predictive of sales for consumer products. 18 In addition, drinking among adolescents and young adults is associated with desirability and identification with characters in alcohol ads 5 and with liking of alcohol ads.…”
Section: Discussionmentioning
confidence: 99%
“…A review of alcohol advertising effects identified 7 studies, none of which included ABM. 4 A subsequent review of 13 longitudinal studies 5 included 2 that focused specifically on ABM 20,21 and 2 that included ABM ownership among a wider range of alcohol marketing exposures. 22,23 The authors concluded that 12 of the 13 studies showed that exposure to alcohol marketing predicts drinking initiation and increased levels of consumption.…”
Section: Jonesmentioning
confidence: 99%